Two‐scale ion meandering caused by the polarization electric field during asymmetric reconnection - Shan Wang; Li‐Jen Chen; Michael Hesse; Naoki Bessho; Daniel J. Gershman; John Dorelli; Barbara Giles; Roy B. Torbert; Craig J. Pollock; Robert Strangeway; Robert E. Ergun; James L. Burch; et al. (Geophysical Research Letters)
Abstract Ion velocity distribution functions (VDFs) from a particle‐in‐cell simulation of asymmetric reconnection are investigated to reveal a two‐scale structure of the ion diffusion region (IDR). Ions bouncing in the inner IDR are trapped mainly by the electric field normal to the current sheet (N direction), while those reaching the outer IDR are turned back mainly by the magnetic force. The resulting inner layer VDFs have counter‐streaming populations along N with decreasing counter‐streaming speeds away from the midplane while maintaining the out‐of‐plane speed, and the outer layer VDFs exhibit crescent shapes toward the out‐of‐plane direction. Observations of the above VDF features and the normal electric fields provide evidence for the two‐scale meandering motion.